Application of mathematical morphology to the quantification of in vitro endothelial cell organization into tubular-like structures - Angulo, J.; Matou, S. (Cellular and Molecular Biology, 2007)
Experiments of in vitro angiogenesis are important tools for studying both the mechanisms of formation of new blood vessels and the potential development of therapeutic strategies to modulate neovascularisation (e.g., screening of new pharmacological molecules). One of the most frequently used angiogenesis assays is the culture of endothelial cells on a reconstituted basement membrane named Matrigel, since the cells constitute a capillary-like network which can be quantified by image analysis. In this paper, a global, robust and fully automated methodology is proposed to segment and quantify in vitro endothelial cell networks from greyscale images using mathematical morphology operators. After extracting the established cell network by means of a top-hat transformation and separating the tubular structures and the cell aggregates by size and shape an interpolation algorithm yields a reconstituted closed network. Using these image data results different kinds of quantitative parameters are calculated: size/shape, morphological distribution, spatial organisation, etc. In this paper, we have established an automatic quantitative analysis to evaluate a modulator effect of a sulphated exopolysaccharide on FGF-2-induced in vitro angiogenesis, according to different parameters. Experimental results allow us to draw a discussion of the pertinence of the alternative morphological parameters to evaluate the characteristics and behaviour of cell cultures.